The Triangle of Sensory Marketing Model: Does it Stimulate Brand Experience and Loyalty? - Alex Fahrur Riza; Dwi Marlina Wijayanti (Esensi: Jurnal Bisnis dan Manajemen, 2018)
The purpose of this study is to examine the framework of brand experience associating with customer loyalty. Sensory marketing effectiveness is recognized in business contexts but only little research has been conducted on sensory marketing. This study contribute to filling this gap by proposing a model that explains how sensory stimulation influences loyalty. Brand experience is expected to mediate this relationship. This study applies exploratory and explanatory approaches to investigate the sensory marketing concept and examine the framework brand experience in association with customer loyalty. Data is collected using online survey. Respondents are individual who had experience in consuming product at restaurant or cafe that has been using the five senses stimulus. Conceptually, this study found interesting relationship between sensory marketing, brand experience, and customer loyalty then called as triangle sensory marketing. The findings offer an additional insight to managers on sensory marketing strategy to stimulate brand experience that can establish customer loyalty.DOI: 10.15408/ess.v8i1.6058